Zarządzanie talentami na przykładzie Wojskowych Zespołów Sportowych oraz Wojskowych Centrach Szkolenia Sportowego = The talent management based on the example of Military Sports Teams and Military Sports Training Centers - Łukasz Malinowski (Kazimierz Wielki University, 2015)
Malinowski Łukasz. Zarządzanie talentami na przykładzie Wojskowych Zespołów Sportowych oraz Wojskowych Centrach Szkolenia Sportowego = The talent management based on the example of Military Sports Teams and Military Sports Training Centers. Journal of Education, Health and Sport. 2015;5(12):622-629. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.44699 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A622-629 http://pbn.nauka.gov.pl/works/693737 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Original Text published © The Author (s) 2015. Malinowski Łukasz. Zarządzanie talentami na przykładzie Wojskowych Zespołów Sportowych oraz Wojskowych Centrach Szkolenia Sportowego = The talent management based on the example of Military Sports Teams and Military Sports Training Centers. Quality in Sport. 2015;1(4):18-27. eISSN 2450-3118.   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.12.2015. Revised 25.12.2015. Accepted: 29.12.2015.   Łukasz Malinowski Akademia Wychowania Fizycznego i Sportu w Gdańsku   Zarządzanie talentami na przykładzie Wojskowych Zespołów Sportowych oraz Wojskowych Centrach Szkolenia Sportowego The talent management based on the example of Military Sports Teams and Military Sports Training Centers       Streszczenie                 Artykuł dotyczy problematyki pozyskiwania talentów dla Wojskowych Centrów Szkolenia Sportowego wraz z opisaniem wsparcia finansowego udzielanego przez Ministerstwo Sportu i Turystyki i ich działania oraz funkcjonowania w Polsce Wojskowych Zespołów Sportowych i ich osiągnięć.   Słowa kluczowe: wojsko, sport, szkolenie, talent       Abstract                 The article concerns the problems of sourcing talent for Military Sports Training Centers, describes the financial support provided by the Ministry of Sport and Tourism. It also describes the operation and achievements of Polish Military Sports Teams.   Key words: army, military, sport, training, talent